3-D TRANSIENT SIMULATION OF A FLAT CAPPILARY HEAT PIPE VIA AN INTERFACE TRACKING METHOD - Machado, H. A. (Revista de Engenharia Térmica, 2006)
In capillary and micro heat pipes the internal porous media is replaced by a capillary groove, yielding a meniscus formed by the liquid phase. The meniscus height varies along the groove length, from the condenser section to the evaporator section, and the difference between the pressures in each extremity is responsible for pumping the liquid. Such devices have been employed in electronic cooling, due its small dimensions. This system provides excellent thermal control, assuring uniform temperature distribution. In previous works related to capillary heat pipe simulation, empirical or simple 1-D models have been used, but not taking into account the complete unsteady phenomena. In this work, the 3-D unsteady simulation of a flat micro heat pipe is presented, where the meniscus radius is considered constant along the transversal section. The phase change problem of a heated liquid meniscus in a groove is simulated via an interface tracking method, which is an hybrid Lagrangean-Eulerian method for moving boundary problems. A variation of the one-dimensional Stephan problem is used to validate the numerical code.